ROLE OF COTTAGE INDUSTRY FOR POVERTY ALLEVIATION IN BANGLADESH: A STUDY - Akter, Jesmin (International Journal of Research -GRANTHAALAYAH, 2025)
Cottage industries in Bangladesh play a significant role in poverty reduction by providing employment and income opportunities, particularly for the rural poor and women. The Bangladesh Small and Cottage Industries Corporation (BSCIC) actively supports these industries, leading to increased household consumption and reduced poverty gaps. Cottage industry refers to the traditional artisanship of the rural people of Bangladesh, who produce various household items using locally available raw materials and artistic skills inherited from past generations. Cottage industries provide economic opportunities for the poor or the middle-income section of people through employment and income generation schemes all over the world, and especially in low-income and technologically underdeveloped countries such as Bangladesh. The objective of the study is to find out the contribution of cottage industry to alleviating the poverty of rural people in Bangladesh. The study adopts a descriptive approach to describe the products as well as the stages of their formation and analyze the relationship between cottage industry and popular heritage. The study found that this industry helps to create employment opportunities and reduce the poverty. The study concludes that cottage industries in Bangladesh face a lot of problems, such as a shortage of working capital, high cost of raw materials, lack of organizing capability, inadequate technology & efficiency, lack of policy support, great knowledge gap, lack of power supply, shortage of credit facilities, infrastructural problems, inadequate government support, low return from production, reduced customer demand, inability to face market competition, lack of social recognition, and lack of social status. The study suggests that increasing capital investment, making good marketing channels, developing product quality, developing infrastructural facilities, meeting immediate needs for the organization of cooperative societies, and motivating the young generation and women to engage in this profession and government patronization are very essential for the development of cottage industries.